Telaah Kebijakan Segregasi Gender di Pesantren Terhadap Ragam Orientasi Seksual Santri - Thoriq Aziz Jayana; Ulfatul Hasna (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: Study of Gender Segregation Policy in Islamic Boarding Schools Towards the Variety of Santri's Sexual OrientationThis study to analyze the gender segregation policy in Islamic boarding schools that have an impact on the development of the sexual orientation of students. The segregation is based on Islamic law, but does not pay attention to aspects of sexual orientation, resulting in the emergence of various sexual orientations which are actually considered abnormal and immoral (in the concept of religion and social construction). This research was conducted at the Fathul 'Ilmi Islamic Boarding School, Madura. The research method uses a qualitative approach with the type of phenomenological research. Data collection techniques using in-depth interviews and observation. While the data processing and analysis techniques used triangulation from the results of interviews and observations. Selection of informants based on purposive sampling. The results showed that: 1) at the Fathul 'Ilmi Islamic Boarding School there is strict gender segregation, 2) there are various sexual orientations of students, namely heterosexual, homosexual, and bisexual. 3) the solution to the problem of student sexual orientation, namely pesantren, needs to make policies that are gender responsive.Abstract: Telaah Kebijakan Segregasi Gender di Pesantren Terhadap Ragam Orientasi Seksual SantriPenelitian ini berupaya menganalisis tentang kebijakan segregasi gender di pesantren yang berdampak pada perkembangan orientasi seksual santri. Segregasi tersebut didasarkan pada hukum Islam, namun tidak memperhatikan aspek orientasi seksual, sehingga akibatnya memunculkan beragam orientasi seksual yang justru dinilai abnormal dan amoral (dalam konsep agama dan konstruksi sosial). Penelitian ini dilakukan di Pesantren Fathul ‘Ilmi, Madura. Metode penelitian menggunakan pendekatan kualitatif dengan jenis penelitian fenomenologi. Teknik pengumpulan data menggunakan wawancara mendalam dan observasi. Sedangkan teknik pengolahan data dan analisis menggunakan triangulasi dari hasil wawancara dan observasi. Pemilihan informan berdasarkan purposive sampling. Hasil penelitian menunjukkan bahwa: 1) di Pesantren Fathul ‘Ilmi melakukan segregasi gender yang ketat, 2) terdapat beragam orientasi seksual santri yakni heteroseksual, homoseksual, dan biseksual. 3) solusi atas permasalahan orientasi seksual santri yakni pesantren perlu membuat kebijakan yang responsif gender.